2016
DOI: 10.1111/jav.01032
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone levels in relation to size and UV reflectance of achromatic plumage traits of female pied flycatchers

Abstract: In a substantial number of species, females show some development of secondary sexual characters. These traits can function as signals of individual phenotypic or genetic qualities and status to conspecifics. Individuals may benefit potentially from expressing signals or badges of status if they are reliable and honest signals of individual quality. In many species, badge sizes have been shown to correlate with dominance rank, which may be mediated by testosterone (T) levels. Here, we explored geographic varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 119 publications
(177 reference statements)
0
19
0
Order By: Relevance
“…In this study we focus on the area of these plumage patches as in other studies of the species (Galván and Moreno 2009, Lehtonen et al 2009a, Moreno et al 2011, Plaza et al 2018. Moreover, we have previously shown that area and UV reflectance of wing patches are positively correlated, at least in females (Cantarero et al 2017). More than half of the females (56% in the study years) exhibit no measurable forehead patch in our populations.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…In this study we focus on the area of these plumage patches as in other studies of the species (Galván and Moreno 2009, Lehtonen et al 2009a, Moreno et al 2011, Plaza et al 2018. Moreover, we have previously shown that area and UV reflectance of wing patches are positively correlated, at least in females (Cantarero et al 2017). More than half of the females (56% in the study years) exhibit no measurable forehead patch in our populations.…”
Section: Introductionmentioning
confidence: 91%
“…Forehead patches are moulted together with body plumage in Africa, while wing patches are constituted by white patches on tertials, also moulted in Africa, and white bands on flight feathers, moulted in the breeding range during or soon after breeding (Lundberg and Alatalo ). The parts of wing patches moulted in the breeding respectively to wintering areas constitute roughly half of the total wing patch each (Cantarero et al ). The expression of achromatic plumage in males varies across the breeding distribution, with males of Spanish populations exhibiting the largest white forehead and wing patches (Lehtonen et al , Laaksonen et al ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The evolution of female ornamental traits has been considered to be a genetically correlated response to selection for male ornamentation (Lande 1980, Amundsen 2000. However, numerous studies show that females acquire fitness advantages by deterring conspecific rivals and/or attracting mates (Amundsen 2000, Morales et al 2007, Hegyi et al 2008, Griggio et al 2009, Roulin et al 2010, Cantarero et al 2017a, Plaza et al 2018, indicating that ornamental trait evolution in females may have its own functionality and can be at least partly explained by sexual selection (Tobias et al 2012). Indeed, there is evidence that female ornamental traits could act as signals of individual quality (Hanssen et al 2006, Morales et al 2007), fecundity (Potti et al 2013) or reproductive investment (Wright et al 2008).…”
Section: Introductionmentioning
confidence: 99%